Rheumatoid neuropathy: a histological and electrophysiological study - Weller, R. O. (1970)
Peripheral nerves in five patients with rheumatoid neuropathy were examined electrophysiologically and by sural nerve biopsy. There was close correlation between the clinical severity of the disease and the degree of nerve damage found histologically and by EMG. Group 1 patients with a mild distal sensory neuropathy showed varying degrees of axonal degeneration in the large myelinated fibres and some segmental demyelination. Group 2 patients with a severe, rapidly progressive sensori-motor neuropathy had extensive loss of myelinated fibres. In one case all the large fibres had degenerated. The second case had lost both large and small myelinated fibres together with many of the non-myelinated axons. The major nerve damage in both groups appeared to be axonal degeneration but some segmental demyelination was detected. Occlusive vascular disease in the vasa nervorum was considered to be the major cause of the nerve damage.